Pembiayaan Defisit APBN menurut Umer Chapra (Studi Analisis Kritik terhadap Pembiayaan Defisit APBN Indonesia Periode 2010-2015) - Djayusman, Royyan Ramdhani; Fatturroyhan, Fatturroyhan (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2017)
The Indonesian State Budget uses the concept of a deficit as a stimulus for economic growth. This deficit is financed by loans, both internally and externally, which contain elements of usury that will eventually lead to inflation and sometimes even lead to recession and economic depression. Meanwhile, conditions that should be deficit are financed in a way that does not contain usury and maintains economic stability. This study aims to determine the deficit financing of the Indonesian State Budget for 2010-2015 and to conduct a critical analysis of the deficit financing of the Indonesian State Budget for 2010-2015 in terms of Umer Chapra's thinking. This study uses a type of literature research, with the method of critical analysis. This research shows that the deficit financing of the Indonesian State Budget in 2010-2015, budget deficit financing comes from two sources, namely debt financing consisting of domestic loans and foreign loans, and non-debt financing consisting of tax revenues, management or privatization of BUMN, and asset management results. From the analysis of criticism of Indonesia's deficit financing, the researcher criticizes 3 elements, namely revenue, financing, and expenditure of the State Budget. The main problem is that the financing of the APBN deficit uses foreign debt instruments that contain elements of usury and weakens the capacity of the subsequent APBN, while there is another alternative, namely the state Sukuk to cover the APBN deficit. In other words, that the foreign debt carried out by the government weakens the APBN itself with its principal debt burden and interest installments. From the non-debt side, the revenue from tax collection that occurs is unfair, and the privatization of BUMNs that occurs is detrimental to the state. Meanwhile, in terms of APBN expenditures for financing have not prioritized public welfare, it can be seen from the 2010-2015 APBN expenditure budget post that has swelled in the military defense budget post.